Letter from Edward F. Hayes to Andrew M. Sessler, January 27, 1978 - Hayes, Edward F.; National Science Foundation (U.S.) (1978)
Edward F. Hayes (1941-) of the National Science Foundation (NSF) informs Andrew M. Sessler of the Lawrence Berkley Laboratory that the NSF approves of the selection of William A. Lester, Jr. (1937-) as the director of the National Resource for Computational Chemistry (NRCC).
Keywords: Sessler, A. M. (Andrew Marienhoff); Hayes, Edward F., 1941-; Lester, William A., Jr., 1937-; Lawrence Berkeley Laboratory. National Resource for Computation in Chemistry; National Science Foundation (U.S.); Chemists; African American chemists